KINERJA EXCHANGE-TRADED FUND (ETF) YANG DIKELOLA SECARA PASIF DAN FAKTOR YANG MEMPENGARUHINYA - Miftahusni,, Nundy; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2021)
The purpose of this study is to analyze the determinants of ETF performance in Indonesia. ETF is an exchange traded mutual fund and traded in the stock exchange around the world. Unlike equity fund actively-manage which has objective to outperform the composite index, ETF is passively manage and trying to replicate the benchmark index performance. This study uses model implemented by Rompotis (2012) who find that the ETF return is determined by its risk, tracking error, and expense ratio. This study examines the performance of 13 passively managed equity ETFs which listed in Indonesia Stock Exchange during 2019. The result indicates that the ETF underperforms its benchmark index. Additionally, this study finds that risk, and expense ratio determine the ETF performance, while net tracking error does not.